The European venture capital landscape: an EIF perspective. Volume II: Growth patterns of EIF-backed startups - Simone Signore (European Investment Fund (EIF), 2016)
Start-up growth is often treated as a stylised fact, despite an extensive research body composed of divergent theories and empirical findings. Against this background, this work contributes to the literature by analysing a hand-collected dataset of 2,951 EIF-backed VC start-ups. Section 2 briefly reviews the relevant literature and 3 discusses data and methods. Section 4 uses descriptive statistics to explore average and median growth trends of start-ups, following an EIF-backed VC investment. Section 5 employs a latent class cluster analysis to establish a taxonomy of start-up growth profiles, characterised by speed and bias towards sales or patenting. The observed growth patterns, described in section 6, are typically idiosyncratic and persistent. However, a series of factors affecting growth mode can be evidenced. In particular, this paper finds that the geographic distribution of outperforming start-ups hints at national and regional factors acting as enablers for different typologies of successful growth. Implications for research and practice are discussed.
Keywords: M13; G24; L25; 330; EIF; start-up growth; venture capital; growth patterns